2018
DOI: 10.1007/s40200-018-0363-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of different metabolic phenotypes of obesity in Iranian children and adolescents: the CASPIAN V study

Abstract: Background Pediatric metabolic disorders are a major health problem. The prevalence of child and adolescent metabolic disorders particularly obesity has globally shown a growing pattern. The aims of this study were to estimate the prevalence of different metabolic phenotypes of obesity in children and adolescents. Methods This multi-centric cross-sectional study was conducted in 2015 in 30 provinces of Iran. Participants consisted of 4200 school students aged 7-18 years, studied in a national school-based surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 27 publications
(24 reference statements)
3
21
1
Order By: Relevance
“…A previous national study reported the prevalence of obesity as 10.9%, MHO as 9.1%, and MUO as 1.8% among children and adolescents in Iran [6]. It means approximately 83.3 and 16.7% of children and adolescents affected by obesity were MHO and MUO, respectively, while in the current study, the prevalence of these phenotypes was 38.8 and 62.2%, respectively.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…A previous national study reported the prevalence of obesity as 10.9%, MHO as 9.1%, and MUO as 1.8% among children and adolescents in Iran [6]. It means approximately 83.3 and 16.7% of children and adolescents affected by obesity were MHO and MUO, respectively, while in the current study, the prevalence of these phenotypes was 38.8 and 62.2%, respectively.…”
Section: Discussioncontrasting
confidence: 49%
“…This further highlights the importance of obesity phenotypes in children and adolescents, since MHO and MUO comprise both excess weight and cardiometabolic RFs. A recent study among children and adolescents in Iran reported the prevalence of obesity, MHO, and MUO as 10.9, 9.1, and 1.8%, respectively [6]. Meanwhile, in the US, approximately 65% of adolescents affected by obesity have the MHO phenotype, while only 32% of adults with excess weight have this phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of MHNO was higher than other groups, followed by MHO, MNHNO, and MNHO, respectively. This finding was in line with previous studies in Iranian children and adolescents (43,44).…”
Section: Discussionsupporting
confidence: 94%
“…Seventy six articles were included in the nal analysis in this meta-analysis. Twenty ve studies were excluded due to the following exclusion criteria: different study population [109][110][111][112][113], no full test [114][115][116][117], unclear diagnostic criteria [118][119][120][121][122][123][124][125], letter to editor [126], written in non English language [127,128], and different study design [129][130][131][132][133] (Fig. 1).…”
Section: Selection Of Eligible Studiesmentioning
confidence: 99%